Measurement performance of activity measurements with newer generation of Apple watch in wheelchair users with spinal cord injury: manually and device-counted pushes [data] - Benning, Nils-Hendrik; Knaup-Gregori, Petra; Rupp, Rüdiger (Universität, 2021)
This dataset contains the results (manually counted pushes and pushes counted by Apple Watch Series 4) of the study presented in the paper "Accurac...